A framework for VSM integrated with Fuzzy QFD. Issue 5 (10th August 2015) - Mohanraj, R.; Sakthivel, M.; Vinodh, S; Vimal, K.E.K.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to apply a framework for value stream mapping (VSM) integrated with fuzzy quality function deployment (QFD) for enabling scientific prioritization of improvement proposals to improve leanness. Design/methodology/approach – The literature was reviewed from the perspectives of VSM, QFD and fuzzy logic applications. The current state map was developed for the case component; fuzzy QFD was used for prioritizing improvement proposals and prioritized proposals were incorporated in the future state map. Findings – The approach enabled the scientific mapping of wastes with improvement proposals and thereby enabling systematic implementation of improvement proposals. The conducted pilot study resulted in 4 percent reduction in cycle time. As the lean implementation is a continuous process, furthermore improvements are expected in near future. Research limitations/implications – The study was conducted in an Indian camshaft manufacturing organization. The improvements in terms of leanness parameters were quantified. Practical implications – The findings determined from the study has practical relevance. Besides, managerial implications were also discussed. Originality/value – The study presented in this paper was conducted in a real time manufacturing environment. Hence the contributions of study are found to be valuable among academic and practicing communities.